Peer influences and intention to smoke e-cigarette: A cross-sectionaL study among form 4 students of a secondary school in Kuantan,Pahang - Latt, Swe Swe; Pasi, Hafizah; Nasreen, Hashima E; Mohd Rus, Razman; Ab Rahman, Jamalludin; Abd. Aziz, Karimah Hanim (Malaysian Public Health Physicians’ Association, 2016)
Although research in high-income countries highlighted that peer influence served as an important factor in the first-time use of e-cigarette among the secondary school students, there is lacking research on the topic in Malaysia. This study measured the prevalence of future intention to smoke e-cigarette and to explore peer influence to be one of the strongest factors among form 4 students. A cross-sectional study was done in Sekolah Menengah Kebangsaan Indera Mahkota 2 (SMKIM 2) in April 2016 among 101 students using assisted self-administered questionnaire. Data were presented as frequencies, percentages and Chi-square test. Almost all of the students (96%) had previously heard of e-cigarette, and the prevalence of ever user and never user was 36.1% and 63.9% respectively. About 28.4% reported that more than half of their friends used e-cigarette. The prevalence of intention to smoke e-cigarette in the next 12 months was 8.2% (n=8). Among them, 87.5% were ever user and 75% male students. Ever user was significantly (p=0.003) indented to use e-cigarette. The prevalence of intention to smoke e-cigarette if offered by best friend was 20.6% (n=20). Both ever user 100% and male students 90% were Significantly (p<0.001) intended to use e-cigarette if offered by a best friend. This study highlighted that peer influence is one of the contributing factors for their future smoking behaviour among the form 4 students at SMK IM2. School health education programme may be one of the effective strategies to prevent smoking e-cigarette too.